2013
DOI: 10.1371/journal.pone.0066890
|View full text |Cite
|
Sign up to set email alerts
|

GNPs-CS/KGM as Hemostatic First Aid Wound Dressing with Antibiotic Effect: In Vitro and In Vivo Study

Abstract: Ideal wound dressing materials should create a good healing environment, with immediate hemostatic effects and antimicrobial activity. In this study, chitosan/konjac glucomannan (CS/KGM) films embedded with gentamicin-loaded poly(dex-GMA/AAc) nanoparticles (giving GNP-CS/KGM films) were prepared as novel wound dressings. The results revealed that the modified CS/KGM films could be used as effective wound dressings and had significant hemostatic effects. With their microporous structure, the films could effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Therefore, wound healing, using this product, can be attributed both to the bactericidal effect and the favoring of wound healing by NO (24) . Other authors were also interested in studying the bactericidal action, according to study A10, which analyzed products as chitosan/glucomannan konjac (GNP-CS/KGM) film, incorporated with gentamicin poly (dex-GMA/AAC) nanoparticles, which identified good antibiotic capacity, as well as a hemostatic effect, shortening the bleeding time and significantly reducing the volume in relation to the control group (25) . Study A11 evaluated the effect of calcium nanoparticles (CNP) on wound healing in rats in topical and intravascular use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, wound healing, using this product, can be attributed both to the bactericidal effect and the favoring of wound healing by NO (24) . Other authors were also interested in studying the bactericidal action, according to study A10, which analyzed products as chitosan/glucomannan konjac (GNP-CS/KGM) film, incorporated with gentamicin poly (dex-GMA/AAC) nanoparticles, which identified good antibiotic capacity, as well as a hemostatic effect, shortening the bleeding time and significantly reducing the volume in relation to the control group (25) . Study A11 evaluated the effect of calcium nanoparticles (CNP) on wound healing in rats in topical and intravascular use.…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al 2013 (25) GNPs-CS/KGM as hemostatic first aid wound dressing with antibiotic effect: In vitro and in vivo study…”
Section: A10mentioning
confidence: 99%
“…The same approach to in vitro testing is likely to have similar significant human health implications (and very possibly commercially-expensive consequences) in the field of nano-medicine and nanosafety testing. In short, the same caveats of physiological relevance and predictive value are likely to apply in the field of nanotoxicology and nano-efficacy testing, with reports of consistency between in vivo and in vitro results from immortalised cell lines (48)(49)(50)(51)(52)(53)(54)(55)(56)(57) being fundamentally compromised by crossspecies extrapolation unjustified by model biochemical divergence.…”
Section: In Vitro Systems: Primary Cells Vs Immortalised Cellsmentioning
confidence: 99%
“…Histological observations showed that these films improved considerably granulation tissue and epithelial coverage (developed by seven and fourteen days of treatment). Fan et al (98) discussed the use of chitosan/konjac glucomannan (CS/KGM) films embedded with antibiotic as a haemostatic wound dressing as another wound care option. Vetvicka and Vetvickova (99) reported that yeast-derived insoluble β (1-3)-D-glucans inhibited strongly adipogenesis, accelerated wound healing and lowered skin irritation.…”
Section: Woundsmentioning
confidence: 99%